Development of the criteria and indicators of Malaysian garden city: a Delphi consensus - Yaman, Amat Ramsa; Mohd, Abdullah; Redzuan, Ma'rof; Aziz, Azlizam (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
It is the aspiration of the Malaysian Government to transform the country into a garden nation by 2020. It is envisaged that in the near future the image of garden nation will be materialized when all cities in the country also portray the garden image in their design and visual. There are no criteria and indicators previously used in developing these garden cities. A study was conducted to develop a reliable set of criteria and indicators for an ideal, garden city for Malaysia. Delphi method was used in this study to solicit the opinion from 30 experts through a series of questionnaire. As a result, this study was able to generate and identifying 8 criteria and 42 indicators for an ideal Malaysian’ garden city. The criteria and indicators identified could be used by the Malaysian agencies and local authorities in assessing and monitoring the development of garden cities in the country